Piezoelectric Energy Harvesting: Enhancing Power Output by Device Optimisation and Circuit Techniques - Worthington, Emma (Cranfield University, 2010)
Energy harvesting; that is, harvesting small amounts of energy from environmental sources such as solar, air flow or vibrations using small-scale (≈1cm 3 ) devices, offers the prospect of powering portable electronic devices such as GPS receivers and mobile phones, and sensing devices used in remote applications: wireless sensor nodes, without the use of batteries. Numerous studies have shown that power densities of energy harvesting devices can be hundreds of µW; however the literature also reveals that power requirements of many electronic devices are in the mW range. Therefore, a key challenge for the successful deployment of energy harvesting technology remains, in many cases, the provision of adequate power. This thesis aims to address this challenge by investigating two methods of enhancing the power output of a piezoelectric-based vibration energy harvesting device. Cont/d.